Triptolide-mediated cell death in neuroblastoma occurs by both apoptosis and autophagy pathways and results in inhibition of nuclear factor–kappa B activity - Krosch, Tara C. K. (Am J Surg, 2013)
BACKGROUND: Neuroblastoma is an aggressive pediatric malignancy with significant chemotherapeutic resistance. We assessed triptolide as a potential therapy. METHODS: SH-SY5Y and IMR-32 neuroblastoma cell lines were treated with triptolide. Viability, intracellular calcium, caspase activation, protein, and mRNA levels were measured. Autophagy was evaluated with confocal microscopy. Nuclear factor–kappa B (NF-κB) activation was measured using a dual luciferase assay. RESULTS: Triptolide treatment resulted in death in both cell lines within 72 hours, with sustained increases in intracellular calcium. IMR-32 cells underwent cell death by apoptosis. Conversely, light chain 3II (LC3II) protein levels were elevated in SH-SY5Y cells, which is consistent with autophagy. Confocal microscopy confirmed increased LC3 puncta in SH-SY5Y cells compared with control cells. Heat shock pathway protein and mRNA levels decreased with treatment. NF-κB assays demonstrated inhibition of tumor necrosis factor (TNF)-α–induced activity with triptolide. CONCLUSIONS: Triptolide treatment induces cell death in neuroblastoma by different mechanisms with multiple pathways targeted. Triptolide may serve a potential chemotherapeutic role in advanced cases of neuroblastoma.